Energy consumption and increased EV range evaluation through heat pump scenarios and low GWP refrigerants in the new test procedure WLTP. (April 2019) - Yu, Binbin; Yang, Jingye; Wang, Dandong; Shi, Junye; Chen, Jiangping
Highlights: The heating energy consumption of a battery electric vehicle was evaluated under the new Worldwide Harmonized Light-duty Test Procedure driving cycle. A heating load prediction model was established and validated with an error within 5%. Heat pump Scenarios lead to 41% - 72% lower energy consumption than PTC. Utilizing moderate recirculation air is a smart way to reduce the overall consumed energy. Driving range extension is between 14.2% and 31% higher than PTC for different heat pumpscenarios studied. Abstract: The aim of this work is to evaluate the cabin heating energy consumption and driving range for a battery electric vehicle. The vehicle was tested in climatic wind tunnel laboratory under Worldwide Harmonized Light-duty vehicle Test Cycle. A heating load model was established and used to predict the heating requirements of the vehicle in different climate conditions. Three different heat pump systems and five refrigerants are also investigated. Results show an error within 5% for the established heating load model. Compared with PTC heating, the heat pump systems lead to much lower energy consumption between 41% and 72% for different scenarios. Besides, 20% and 30% recirculation air can reduce the overall consumed energy by an average of 28.5% and 36.6%, respectively. Finally, the driving range of all the heat pump systems are much higher than that of PTC, which is between 14.2% and 31%.